2018
DOI: 10.15640/jaes.v7n2a17
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ knowledge and perception of the use of pesticides in Arabica coffee, Coffea arabica agro-ecologies of Uganda

Abstract: Low yields of coffee in Uganda are due to a number of factors with insects, diseases and weeds being paramount. In response, farmers respond by applying all kinds of pesticides to control these stresses. A questionnaire to elucidate farmers' knowledge and perceptions of pesticide use was therefore administered to 325 randomly selected respondents in the Arabica coffee growing regions of Uganda. Our results showed that only 23% of the respondents had ever used or were using pesticides, although, >50% of these r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
(78 reference statements)
3
3
0
Order By: Relevance
“…5,66 Dzobo 50 found that farmers complained about the following: body weakness (89.2%), sexual weakness (ie, impotence) among the men (24.5%), chronic cough (15.4%), and depression (14.3%) as symptoms of chemical poisoning. Similar findings have been reported in Uganda 14 and Kenya. 63 Study participants also lacked access to recommended protective gear: overall coats, nose masks, Wellington boots, and gloves.…”
Section: Chemical Poisoningsupporting
confidence: 91%
See 3 more Smart Citations
“…5,66 Dzobo 50 found that farmers complained about the following: body weakness (89.2%), sexual weakness (ie, impotence) among the men (24.5%), chronic cough (15.4%), and depression (14.3%) as symptoms of chemical poisoning. Similar findings have been reported in Uganda 14 and Kenya. 63 Study participants also lacked access to recommended protective gear: overall coats, nose masks, Wellington boots, and gloves.…”
Section: Chemical Poisoningsupporting
confidence: 91%
“…Their study further found that farmers do not observe basic safety precautions such as re-entry period and most farmers spray pesticides against the wind, a finding that confirm the earlier study in Uganda. 14 The present study also observed that farmers engage in dangerous practices, such as mixing fertilizer and herbicides, with the hope that the concoction can kill weeds and at the same time provide nutrients to their crops. The result, therefore, affirms the findings of Mattah et al 51 who discovered that farmers used a cocktail of pesticides to control pests.…”
Section: Chemical Use Practices and Safety Precautions Among Smallhol...supporting
confidence: 51%
See 2 more Smart Citations
“…For instance, Kwakye et al (2019) reported that in Ghana 89% farmers' stored pesticides in their home and 76% of them use products immediately. Similarly, Godfrey et al (2018) reported that more than 60% of coffee producer farmers in Uganda storing pesticides in their homes and 25% of respondents store in their bedrooms. In Ethiopia, different studies showed that farmers store pesticides in different locations.…”
Section: Perception On Pesticide Storagementioning
confidence: 99%